Group-Based Adaptive Rendering System for 6DoF Immersive Video Streaming - Soonbin Lee; Jong-Beom Jeong; Eun-Seok Ryu (IEEE Access, 2022)
The Moving Picture Experts Group (MPEG) has started an immersive media standard project to enable multi-view video and depth representation in three-dimensional (3D) scenes. The MPEG Immersive Video (MIV) standard technology is intended to provide a limited 6 degrees of freedom (DoF) based on depth map-based image rendering (DIBR). The 6DoF immersive video system is still challenging because multiple high-quality video streams require high bandwidth and computing resources. This paper proposes a group-based adaptive rendering method for 6DoF immersive video streaming. With group-based MIV, each group can be transmitted independently, which enables adaptive transmission depending on the user’s viewport. The proposed method derives weights from groups for view synthesis and allocates high-quality bitstreams according to a given viewport. This paper also discussed the results of the group-based approach in the MIV, and the advantages and drawbacks of this approach are detailed. In addition, pixel rate constraint analysis has been introduced to facilitate deployment with existing video codecs. On end-to-end evaluation metrics with TMIV anchor, the proposed method saves average 37.26% Bjontegaard-delta rate (BD-rate) on the peak signal-to-noise ratio (PSNR).